Immune response in ofatumumab treated multiple sclerosis patients after SARS-CoV-2 vaccination - Faissner, Simon; Heitmann, Neele; Plaza-Sirvent, Carlos; Trendelenburg, Paulina; Ceylan, Ulas; Motte, Jeremias; Bessen, Clara; Urlaub, Doris; Watzl, Carsten; Overheu, Oliver; Reinacher-Schick, Anke; Hellwig, Kerstin; et al. (Frontiers in Immunology, 2022)
Objective The pandemic induced by SARS-CoV-2 has huge implications for patients with immunosuppression that is caused by disorders or specific treatments. Especially approaches targeting B cells via anti-CD20 therapy are associated with impaired humoral immune response but sustained cellular immunity. Ofatumumab is a human anti-CD20 directed antibody applied in low dosages subcutaneously, recently licensed for Multiple Sclerosis (MS). Effects of early ofatumumab treatment on alterations of immune cell composition and immune response towards SARS-CoV-2 are incompletely understood. Methods We here investigated immune cell alterations in early ofatumumab (Ofa) treated patients and effects on humoral (titer, neutralization capacity against wild type, Delta and Omicron) and cellular immune responses in Ofa treated MS patients following a third vaccination against SARS-CoV-2 compared to healthy controls. Results We show that a mean treatment duration of three months in the Ofa group led to near complete B cell depletion in line with altered composition of certain CD4+ T cell subpopulations such as enhanced frequencies of naive and a decrease of non-suppressive regulatory T cells (Tregs). Titer and neutralization capacity against SARS-CoV-2 variants was impaired while cellular immune response was sustained, characterized by a strong T helper 1 profile (Th1). Interpretation In summary, low dosage ofatumumab treatment elicits sustained depletion of B cells in line with alterations of immune cells, mainly Tregs. This is associated with impaired humoral immune response towards SARS-CoV-2 vaccination but preserved, Th1 driven cellular immunity adding crucial information regarding early effects of low dosage anti-CD20 therapy on humoral and cellular immunity.